(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasing use of social media as a source of information has changed the way parents obtain information and determine school choices, so that Electronic Word of Mouth (e-WOM) has become one of the factors suspected of influencing these decisions. This study aims to analyze the influence of Electronic Word of Mouth (e-WOM) on parents’ decisions in choosing Darul Mahdiyah School in Tha Chamuang, Southern Thailand. The study used a quantitative approach with a survey method. The study population was 820 parents, while a sample of 89 respondents was determined using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression analysis, coefficient of determination (R²) test, and significance test with the help of IBM SPSS. The results showed that Electronic Word of Mouth (e-WOM) had a positive and significant effect on parents’ decisions in choosing schools with a significance value of 0.000 (<0.05), a regression coefficient of 0.966, and a coefficient of determination (R²) of 0.648. These findings indicate that information, experiences, and recommendations conveyed through social media contribute to building trust and influence parents’ decisions in choosing educational institutions. This research provides empirical evidence on the importance of e-WOM-based digital communication strategies as an effort to improve the image and competitiveness of educational institutions in the digital age.